Simultaneous Influence of Imperfect Length and Load on the Dynamic Buckling of Plane Trusses under Step Loading - Van, Tran Thi Thuy; Tien, Dao Ngoc; Hien, Ta Duy (Engineering, Technology & Applied Science Research, 2024)
The influence of imperfections in element length and loading on the dynamic buckling of plane trusses is investigated in the present study. Finite element formulation and the Euler formula are employed to tackle the problem of large displacements. Equivalently, the Newmark integration method and the Newton–Raphson iteration algorithm are deployed to solve the nonlinear dynamic equilibrium equations. The dynamic applied load considered in this study is a step-imperfect load with an imperfection in the element length. The relationship between the load and maximum displacement is determined, and the simultaneous influence of the imperfect parameters on the dynamic limit load is discussed. The imperfect element length and loading significantly affect the dynamic limit load, demonstrating the need to consider both imperfections when studying the dynamic buckling of truss systems.